Silent atrial fibrillation: clinical management and perspectives - Guenancia, Charles; Garnier, Fabien; Fichot, Marie; Sagnard, Audrey; Laurent, Gabriel; Lorgis, Luc (Future cardiology, 2020)
Silent atrial fibrillation (AF) is an asymptomatic atrial arrhythmia that can be diagnosed by chance during a systematic electrocardiogram, an external Holter, or from implanted cardiac devices. There is a significant body of the literature around silent AF, yet it remains largely underdiagnosed in everyday clinical practice. Meanwhile, new diagnostic tools have significantly improved the detection of silent AF, creating a potential for mass screening via new technologies and the promise of a major step forward in e-health progress. However, it is not yet known whether silent AF is associated with the same thromboembolic risk as symptomatic AF, and whether these asymptomatic and often short-lasting episodes therefore require anticoagulation therapy and rhythm management.